2021
DOI: 10.1080/19476337.2021.1905721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-temperature cooking on the gamma-aminobutyric acid content and antioxidant capacity of germinated brown rice (Oryza sativa L.)

Abstract: Germinated brown rice (GBR) has a high gamma-aminobutyric acid (GABA) content and antioxidant capacity; however, the effects of high-temperature cooking on these characteristics are unclear. We investigated alterations in GABA content, antioxidant capacity, 15 proteinogenic amino acids, TP and reducing sugar content, and color of cooked GBR at 105°C to 135°C and at different times (40 to 90 min) at 105°C. The contents of GABA and 9 proteinogenic amino acids decreased via thermal decomposition with increasing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…Although soaking for 24 h has been reported to increase the antioxidant capacity of some BR varieties (Owolabi et al, 2018), the findings reported herein showed a reduction in antioxidant capacity compared with untreated BR (control group). This was consistent with the findings of our previous study (Toyoizumi et al, 2021).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Although soaking for 24 h has been reported to increase the antioxidant capacity of some BR varieties (Owolabi et al, 2018), the findings reported herein showed a reduction in antioxidant capacity compared with untreated BR (control group). This was consistent with the findings of our previous study (Toyoizumi et al, 2021).…”
Section: Resultssupporting
confidence: 94%
“…DPPH radical‐scavenging activity was determined as described by Toyoizumi et al (2021). Briefly, 0.25 g of powdered samples were diluted fourfold with an 80% v/v acetone solution and extracted by stirring for 1 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Toyoizumi et al [ 59 ] reported a decrease in the GABA content and most amino acids when cooking germinated brown rice at high temperatures (105 °C, 115 °C, 125 °C, and 135 °C) for 40 min. Therefore, there was a thermal decomposition of these compounds.…”
Section: Resultsmentioning
confidence: 99%